Corporeidade e humanescência na fonte dos saberes da vida: a formação de professores que valoriza o ser - Câmara, Tereza Cristina Bernardo da (2005)
The present study comes from inquietudes of an investigative posture assumed by a Physical Education Graduation Professor, before her educative action with undergraduate teachers. The research was done with 16 (sixteen) Kindergarten and Elementary School teachers, who teach at public schools. The referred teachers are undergraduate students of the Graduating Normal Course at Superior Educational Institute President Kennedy, in Natal/RN. The analysis and discussion of the intertwining of knowledge, within the four Pillars of Education, at the Fountain of Knowledge , is a metaphor, especially created for this study, as for its epistemological and methodological structure, guiding all the investigative process. It provided to show up the repercussion of bathing and drinking these humanizing waters of a pedagogical practice that values the Being, aiming his self-transcendence. The conclusions obtained were the following: 1) The professor, while bathing himself in the Fountain of Life Knowledge, reflects his personal and professional life, recalling feelings and emotions that through time were forgotten, but as they were remembered and lived again, impulse people towards humanity. 2) While bathing himself at the Fountain of Life Knowledge, the professor realizes he is awoken to humane knowledge, caring about his practices, which he develops in the classroom. Practices he considers the learning of knowing, of doing, of living together, and of learning how to be, having and integrated form on the Being. 3) When the worries about the developing of the Being exist coming from the undergraduate teacher there is a practice the shows up the web of corporeity knowledge knowing how to play, how to create, how to feel, how to think, and how to humanize. 4) The presence of the professional of Physical Education, with knowledge and experience of the budgets of corporeity, is essential in the process of graduating the Kindergarten and first years of Elementary School undergraduate teacher, for he, the former, has a huge responsibility as to the learning and developing of the educational process the humanizing developing of the Being In a proposal of education that occurs through the whole life. 5) The Professional of Physical Education has positions to conquer, for the existent gap in the educational process, as for the understanding of the body and of corporeity in the perspective of totality, urges to be modified in name of another mankind, with full humanity